Strengthening the Capacity of AIDS Care Volunteers for Community-Based Homecare: A Participatory Pathway to Stigma Reduction and Social Transformation - Wilandika, Angga; Sari, Diah Nur Indah; Cahyati, Sinta (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
HIV-related stigma remains a major barrier to effective homecare for people living with HIV (PLHIV). This community service program focused on empowering AIDS Care Volunteers in Bandung, Indonesia. The program aimed to enhance knowledge, caregiving skills, and social acceptance toward PLHIV. Thirty AIDS care volunteers participated in a capacity strengthening workshop co-designed and implemented using a Community-Based Participatory Research (CBPR) approach. Activities included participatory learning sessions, role-play simulations, group reflections, and collective action planning. Evaluation combined pre–post testing and qualitative reflections. Results showed significant improvements in HIV knowledge (t = –7.60, p<0.001) and social acceptance (Z = –4.026, p<0.001). Participants also demonstrated increased critical awareness, emergence of local leadership, and stronger collaboration with the Bandung City AIDS Commission. These outcomes highlight the potential of community-based empowerment programs to reduce stigma and strengthen sustainable HIV care.